The Effect of Wushu Routine Training on Basic Movement Patterns in Children (Contemporary Education and Teaching Research, 2025)
This study aimed to evaluate the fundamental movement patterns of elementary school students using the Functional Movement Screen (FMS) and assess the effectiveness of the Wushu routine training program. A total of 164 fifth-grade students (83 in the experimental group and 81 in the control group) underwent an 8-week course teaching experiment. The experimental group participated in the Wushu routine training program, while the control group engaged in regular physical education training. Descriptive statistics, t-tests, and simple correlation analyses were utilized to analyze the data. Results demonstrated that both training programs significantly improved students' FMS scores and reduced the low score rate and asymmetry rate. However, the Wushu routine training showed a more pronounced effect on enhancing the FMS scores compared to conventional physical education training. It was concluded that the five-step fist routine training effectively enhances the functional movement screening scores and optimizes the basic movement patterns of students.